Computer-Aided Diagnosis System for Alzheimer’s Disease Using Different Discrete Transform Techniques - Dessouky, Mohamed M.; Elrashidy, Mohamed A.; Taha, Taha E.; Abdelkader, Hatem M. (American journal of Alzheimer's disease and other dementias, 2016)
The different discrete transform techniques such as discrete cosine transform (DCT), discrete sine transform (DST), discrete wavelet transform (DWT), and mel-scale frequency cepstral coefficients (MFCCs) are powerful feature extraction techniques. This article presents a proposed computer-aided diagnosis (CAD) system for extracting the most effective and significant features of Alzheimer’s disease (AD) using these different discrete transform techniques and MFCC techniques. Linear support vector machine has been used as a classifier in this article. Experimental results conclude that the proposed CAD system using MFCC technique for AD recognition has a great improvement for the system performance with small number of significant extracted features, as compared with the CAD system based on DCT, DST, DWT, and the hybrid combination methods of the different transform techniques.